LAHAN PERTANIAN PANGAN BERKELANJUTAN DI KABUPATEN INDRAGIRI HILIR - KMS Novyar Satriawan Fikri; Mulono Apriyanto; Rifni Novitasari (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2021)
Food agricultural land is the part of the cultivation function land. The population growth rate in Indragiri Hilir Regency reaches 4.66 percent per year. The increase in population growth in Indragiri Hilir Regency has an impact on increasing the need or demand for food which is quite high. From these problems, this study was prepared by identifying the Areas of Sustainable Food Agriculture (LP2B). The purpose of this research is to know the juridical basis, the philosophical basis and the sociological basis. It is concluded that there will be serious problems with the decrease in the area of ​​agricultural land. Lahan pertanian pangan merupakan bagian dari lahan fungsi budidaya. Laju pertumbuhan penduduk di Kabupaten Indragiri Hilir mencapai 4,66 persen per tahun, Peningkatan pertumbuhan penduduk di Kabupaten Indragiri Hilir berdampak pada peningkatan kebutuhan atau permintaan (deman) pangan yang cukup tinggi. Dari pokokpermasalahan tersebut disusunlah studi ini dengan mengidentifikasi Kawasan Lahan Pertanian Pangan Berkelanjutan (LP2B). Adapun tujuan dari penelitian ini mengetahui landasan yuridis, landasan filosofis dan landasan sosiologis. Disimpulkan bahwa akan terjadi permasalahan serius dengan penurunan luas lahan pertanian.